Determinan Terjadinya Pernikahan Usia Dini Serta Dampaknya Terhadap Keluarga Dan Masyarakat - Miftahul Jannah; Sukri Palutturi; Muhammad Syafar (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: The phenomenon of early marriage is still happening even though the law has prohibited it. Early marriage occurs because of educational factors, promiscuity, economics, and cultural norms. Objective: To determine the determinants of the occurrence of early marriage and the impact on the family and society. Methods: Descriptive research design is research conducted with a purpose. The research location is in the District of Rilau Ale, Bulukumba Regency with a total sample of 42 people. Data were processed using SPSS with univariate, bivariate, and multivariate analysis. Results: Based on the results, it was found that there was an early marriage because almost all respondents experienced promiscuity as many as 22 (52.38%), cultural norms that could be trusted were 28 (66.67%) while those who could not be trusted were 14 (33, 33%). Conclusion: that the economic factors that have an influence on the occurrence of early marriage. To religious leaders, community leaders, and government officials to further dig up information and health education for teenagers about early marriage.